Wounded Healers: Job Termination in Faith Community Nursing. Issue 2 (April 2021) - Ziebarth, Deborah Jean; Knighten, Mary Lynne
ABSTRACT: Research regarding faith community nursing termination is scarce. Ziebarth (2018) surveyed faith community nurses (FCNs) who had experienced termination of their position. This article explores FCN feelings related to termination and provides an evidence-based practice component to translate the research into practice. Given that FCNs engage in deep relationships with clients, their feelings following termination express grief and lack of support. Support strategies as well as preemptive strategies that may be useful to prevent loss of an FCN position or ministry are presented.